Explanation of the Benefits and Challenges of Home Care Plan after Hospital Discharge: A Qualitative Study - Zeinab Hashemzadeh; Farhad Habibi; Hossein Dargahi; Mohammad Arab (پیاورد سلامت, 2023)
Background and Aim: Home care is an alternative method of hospitalization, especially for chronic patients and is an innovative approach to improve care and reduce the costs of hospital readmissions. The present study was conducted with the aim of investigating the benefits and challenges of implementing the home care plan after being discharged from the hospital considering the perspective of health service recipients and providers at Tehran University of Medical Sciences in 2021. Material and Methods: The present study is an applied research that was conducted qualitatively using structured and semi-structured interviews. The research sample was those responsible for the implementation of this project at the ministry and university level, the implementers of this project in 4 hospitals, 5 institutions providing home care services, and family of patients. Twenty-eight people from the research community were included in the study using the purposeful and snowball sampling method. Content analysis method was used to analyze the interview data. MAXQDA2020 software was used for data classification. Results: The results were classified into two categories: benefits and challenges of the home care plan after discharge. A total of 61 open codes were extracted from the analysis of research interviews, so that 27 codes led to the identification of 5 themes (Including improving service delivery, reducing costs, achieving health goals, cultural and social benefits, providing the necessary infrastructure) in the benefits and 34 codes led to the identification of 7 themes (including policy-making, legal and ethical, economic, manpower, cultural-social-communication, service provision limitations and time and place limitations) in the challenges. Conclusion: The result of this research showed that home care services after being discharged from the hospital play an important role in completing the provision of healthcare services. Home care services after being discharged from the hospital improves service delivery, reduces costs, and helps in achieving health goals. It also benefits patients, society and the government in various cultural and social fields. On the other hand, it seems that there are challenges in the political, legal, economic and cultural fields in the way of the optimal implementation of this plan. Therefore, planning to evaluate and solve the problems facing these services is essential.